"Unhappy Forever". Method and Issues in Material and Written Records for Me- dieval Archaeology - Galbán Malagón, Carlos (Madrygal. Revista de Estudios Gallegos, 2024)
The divergence between disciplines has led to a growing misunderstanding among researchers based on the nature of the sources, often forgetting the necessity of a non-aprioristic approach to the common record. We present the problems and possibilities of such approach using various examples from the Galician Middle Ages: written documents as objects, relationship between concept and materiality of the architecture of power or the study of seigneurial landscapes. Thus integrating written sources as part of the material record.